Perbandingan Efektivitas Ekstrak Daun Chromolaena Odorata Dan Povidone Iodine 10% Terhadap Kepadatan Kolagen Pada Luka Insisi Tikus Putih (Spraguedawley) - Binsasi, Richarda Anggraini; Telussa, Arley Sadra; Damanik, Efrisca M (Cendana Medical Journal, 2023)
Background: Wound is a discontinuity or damage in part of human tissue. The uses of traditional medicine for the treatment of wound were still commonly found in especially indonesia. One of the tradisional medicine is Cromolaena Odorata. Chromolaena odonarata may promote wound healing and also increases collagen expression. Povidone iodine was currently the standard treatment for wound and has an antiseptic effect. Aim: To understand the comparison of the effectivity of Chromolaena odonarata and Povione iodine 10% to collagen density in incision wound in white mice (Sprague dawley). Method: This is an experimental study with 4 groups which were the control group (P1) which was treated with Povidone iodine 10% and comparison group (P1,P2,P3) which was treated chromolaena odorata 10%,15% dan 20%. Collagen density was measured under the microscope using Nagaoka criteria. Data was analyzed using Kruskall Wallis analysis. Result: The result of this study was p value of p=0.609 (>0.05). Conclusion: The use of Chromolaena odonarata leaf extract and povidone iodine 10% did not showed any significant difference of effectivity in prior to collagen density in incision wound in white mice from Sprague dawley strain.